UZBEKISTAN IN INTERNATIONAL SPORTS FIELDS DURING THE YEARS OF INDEPENDENCE AND ITS SOCIAL SIGNIFICANCE - Tishabaev Alisher Makhkamjonovich (Modern American Journals, 2025)
This article analyzes one of the important stages in the development of physical education and the sports industry in Uzbekistan during the years of independence, focusing on the activities of the “Yoshlik” sports society. It examines government decisions and their implementation, which have led to increased participation in sports—particularly among youth and girls—and to notable international achievements. The study also explores the socio-spiritual role of this society in the lives of citizens.
Keywords: Physical education, sports policy, globalization, chess, healthy lifestyle, competition, international, public.